The state of food security and nutrition in Myanmar 2022: Findings from four rounds of the Myanmar Household Welfare Survey - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The state of food security and nutrition has deteriorated in Myanmar in 2022. Four percent of households were in moderate to severe hunger in October/December 2022. Hunger was highest in Chin (10%), Mon (6.8%), and Kayin (6%). Households with a low food consumption score increased from 9.4% in December 2021/February 2022 to 15.7% in October/December 2022. The shares in October/December were highest in Chin (48.3%), Kayin (23.1%), and Magway (22.7%). Inadequate diet diversity among adults rose from 20.6% to 25.1% over the same period with rates higher for women, especially in rural areas. Decreases in diet quality among adults is driven by lower consumption of milk and dairy products as well as Vitamin A rich fruits, meat, fish, and eggs. More than a third of all children aged 6-23 months and 15.9% of all children aged 24-59 months have inadequate diet quality. Regression analysis reveals low income and limited assets to be important risk factors for food security and adequate diet quality. Wage workers and low wage communities are found to be particularly vulnerable. Rising food prices, conflict and physical insecurity increase the likelihood of poor diet quality. Receiving remittances is a source of resilience; remittance-receiving households are less likely to experience hunger or poor dietary diversity at the household, adult, and child level.